FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN NASABAH DALAM MENABUNG DI BANK MANDIRI SYARIAH PAREPARE - Syahruni, Syahruni; Nuryadin, Rusmin (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine what influences a customer's decision to save at Bank Mandiri Syariah Parepare. The data collected by distributing questionnaires to a study sample of 114 respondents. Data processing using statistical tools SPSS 21. The results provided that the product has a positive impact on customer decisions with a regression coefficient of 0.137. The promotion has a positive effect on customer decisions with a regression coefficient of 0.129. Then, service has a positive influence on customer decisions with a regression coefficient of 0.584. the location has a positive effect on customer decisions with a regression coefficient of 0.112.